Produção de chicória da amazônia cultivada sob densidades de cultivo e poda do pendão floral - Gomes, Rafaelle Fazzi [UNESP]; Silva, Josiane Pereira da [UNESP]; Lopes de Gusmao, Sergio Antonio; Souza, Gisele Teixeira de (Univ Fed Rural Semi-arido-ufersa, 2013)
Chicory is a vegetable Amazon unconventional flavor that has attracted the attention of researchers for its great versatility, which makes it a promising vegetable. However, jobs are scarce in the literature on cultivation techniques for the species. This study aimed to evaluate the effect of pruning tassel floral and different spacing, the yield on Amazon chicory. Three different spacings: E1 = 0.15 x 0.15 m, with 44 plants m(2), E2 = 0.20 x 0.20 m, with 25 plants m(2), and E3 = 0.25 x 0.25 m, with 16 plants m(2), with and without pruning floral tassel. The experiment was conducted in a randomized block design in a split plot design 3 x 2, with six replications. The characteristics evaluated were: number of leaves, fresh weight and dry weight of shoots, number of tassel floral tassel floral fresh weight, yield (kg m(-2)), and leaf area index (LAI). The largest production of chicory Amazon was obtained in plants grown at a spacing of 0.25 x 0.25 m subjected to pruning floral tassel. The highest yield for Amazon chicory was obtained in plants grown at a spacing of 0.15 x 0.15 m submitted pruning floral tassel.

A chicória da Amazônia é uma hortaliça não convencional condimentar que vem despertando a atenção de pesquisadores pela sua grande versatilidade, o que a torna uma hortaliça promissora. Porém, ainda são escassos trabalhos na literatura nacional sobre técnicas de cultivo para a espécie. Assim, este trabalho teve como objetivo avaliar o efeito da poda do pendão floral e de diferentes espaçamentos, no rendimento de chicória da Amazônia. Foram avaliados três espaçamentos: E1= 0,15 x 0,15 m, com 44 plantas m2; E2= 0,20 x 0,20 m, com 25 plantas m2; e E3 = 0,25 x 0,25 m, com 16 plantas m2, sem e com poda do pendão floral. O experimento foi conduzido em blocos casualizados, em esquema de parcela subdividida 3 x 2, com seis repetições. As características avaliadas foram: número de folhas, massa fresca e massa seca da parte aérea, número de pendões florais, massa fresca dos pendões florais, produtividade (kg m-2), e índice de área foliar (IAF). A maior produção de chicória da Amazônia foi obtida nas plantas cultivadas no espaçamento de 0,25 x 0,25 m e submetidas a poda do pendão floral. A maior produtividade de chicória da Amazônia foi obtida nas plantas cultivadas no espaçamento de 0,15 x 0,15 m e submetidos a poda do pendão floral.
Production chicory amazon cultivated under density planting and pruning of floral tassel
Keywords: Eryngium foetidum L.; Spacings; Condimental vegetable; Protected cultivation